2021
DOI: 10.25259/sni_150_2021
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the pandemic on neurosurgical services: A study from a coronavirus disease 2019 referral hospital in Surakarta

Abstract: Background: A decrease in hospital visits including neurosurgery cases during the coronavirus disease 2019 (COVID-19) pandemic has been reported by many countries. This study aims to reveal important data regarding the effect that the COVID-19 pandemic has on services, neurosurgical surgery, and inpatients before and during the COVID-19 pandemic. Methods: This comparative study compares neurosurgical services, neurosurgical patients, outpatient visits, and monthly inpatients assessed from January to Decemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…[ 14 , 30 ] In developing countries including Morocco, where there is a chronic shortage of neurosurgeons, nurses or other skilled health workers, any additional pressure on health-care systems arising from the looming pandemic becomes almost unmanageable. [ 11 , 23 , 29 ] Many of the recommendations published by other neurosurgical centers could not be achieved given the local limitations and resources. [ 16 ] According to a survey about how Africa’s neurosurgical community has been affected by COVID-19, only 52 (16.5%) of the respondents stated they had a specific COVID-19 neurosurgery policy and only 49% felt that their response plans were satisfactory for their neurosurgical services.…”
Section: Discussionmentioning
confidence: 99%
“…[ 14 , 30 ] In developing countries including Morocco, where there is a chronic shortage of neurosurgeons, nurses or other skilled health workers, any additional pressure on health-care systems arising from the looming pandemic becomes almost unmanageable. [ 11 , 23 , 29 ] Many of the recommendations published by other neurosurgical centers could not be achieved given the local limitations and resources. [ 16 ] According to a survey about how Africa’s neurosurgical community has been affected by COVID-19, only 52 (16.5%) of the respondents stated they had a specific COVID-19 neurosurgery policy and only 49% felt that their response plans were satisfactory for their neurosurgical services.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, all eight surgery departments had undergone the protocol, followed the American College of Surgeons and the hospital SOP [11]. A study conducted by Setyono et al observed neurosurgery department in Moewardi Hospital found that the number of inpatients, neurosurgical patients, and outpatients decrease compares with 2019 and 2020 [5]. Surgical procedures are teamwork; all health workers involved have a role in carrying out an operation, from registration, outpatient consultation, hospitalization, radiological investigations and examinations, anesthetic procedures, definitive surgery, post-operative care, and sanitation and disinfection measures for this virus.…”
Section: Discussionmentioning
confidence: 99%
“…Dr. Moewardi Regional General Hospital has supporting facilities for handling COVID such as intensive care unit, isolation ward for patient with infectious diseases, tertiary referral hospital, and the main academic affiliated hospital of the Sebelas Maret University, Faculty of Medicine, Surakarta. The hospital provides a high volume of health-care services for a wide range of many cases [5].…”
Section: Standard Protocol For Managing Surgical Patientsmentioning
confidence: 99%
“…11,12,17 Research comparing the availability of a COVID-19-free operation route with the unavailability of a COVID-19free operating route found that the post-operative patient SARS-CoV-2 infection rate was lower level in the COVID-19-free operation route. 12,18,19 It should be noted that COVID-19 infection without a COVID-19free surgical route in post-operative patients is around 5% with a mortality rate of 25%. However, this infection and mortality rate can drop to 0% with the COVID-19free operating route.…”
Section: Discussionmentioning
confidence: 99%
“…11 In other research of emergency orthopedic patients during the pandemic period from January to December 2020 decreased compared to visits in the same period in 2019 so that orthopedic services at tertiary and academic referral hospitals experienced a significant decrease in cases. 18 However, it is necessary to carry out a follow-up review regarding the variations in lung complications that occur in this research study, both in the period before and during the pandemic.…”
Section: Discussionmentioning
confidence: 99%